Analysis of topologies and key players in terrorist networks. (December 2016) - Ozgul, Fatih
Abstract: While topologies and key player positions and roles differ across terrorist networks, similar ideological networks share similar structures and topologies, maintaining structural properties of their predecessor groups. In this study, we look at basic ideological waves of terrorism in history, classify terrorist network ideologies, and describe the patterns in network topologies and key player characteristics. We show that ideological differences in terrorist networks in part explain the differences in the structure of links between key players.